1995
DOI: 10.1142/s021797929500015x
|View full text |Cite
|
Sign up to set email alerts
|

From Free Clusters to Cluster-Assembled Materials

Abstract: In this paper the specific properties of free clusters and the formation of new cluster-assembled materials using the low energy cluster beam deposition (LECBD) technique are discussed. Recent results obtained for free clusters are summarized with special attention to new observed structures. As for the specific structures and properties of cluster-assembled materials, two main aspects are specially emphasized: the memory effect of the free cluster properties leading to the formation of new phases and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
131
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(137 citation statements)
references
References 0 publications
6
131
0
Order By: Relevance
“…3 suggests that the films are porous [58,67], which is interesting to keep one of the peculiarities of the clusters : their high surface/volume ratio which affects all the physical (structural, electronic) properties as well as the chemical reactivity (catalysis). Concerning deposition of carbon clusters, experiments [13,20] as well as simulations [68] have shown that the carbon clusters preserve their identity in the thick film. Another interesting type of nanostructured film grown by cluster deposition is the growth of cermets by combining a cluster beam with an atomic beam of the encapsulating material [69].…”
Section: Low Energy Clustersmentioning
confidence: 98%
See 3 more Smart Citations
“…3 suggests that the films are porous [58,67], which is interesting to keep one of the peculiarities of the clusters : their high surface/volume ratio which affects all the physical (structural, electronic) properties as well as the chemical reactivity (catalysis). Concerning deposition of carbon clusters, experiments [13,20] as well as simulations [68] have shown that the carbon clusters preserve their identity in the thick film. Another interesting type of nanostructured film grown by cluster deposition is the growth of cermets by combining a cluster beam with an atomic beam of the encapsulating material [69].…”
Section: Low Energy Clustersmentioning
confidence: 98%
“…Ideally, by depositing the clusters with low kinetic energies, one would like to conserve the memory of the free cluster phase [13] to form thin films with original properties. Since the kinetic energy is of the order of 10 eV per cluster [66], i.e.…”
Section: Low Energy Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Over the past few years renewed effort on the preparation and understanding of the properties of clusters deposited in a matrix 2 or on a surface 3 has been undertaken, in the hope of forming nanostructures with a well-defined shape and number of atoms. Deposition at low energy of size-selected clusters on a solid substrate is well suited to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%